Unlocking potential: an assessment of small-scale aquaculture viability in the Lake Victoria Basin, Uganda - Byabasaija, Syliver; Limuwa, Moses; Semyalo, Ronald (Springer International Publishing, 2025)
Despite small-scale pond aquaculture being a vital component of the Lake Victoria Basin communities, its viability is not known. In this study, we examined the viability of small-scale pond aquaculture in the districts of Mpigi, Buikwe, and Wakiso in Uganda, focusing on social-economic and technical aspects. Employing a mixed-methods approach, including household surveys and focus group discussions with 169 fish farmers, the study assessed the effectiveness and sustainability of small-scale pond aquaculture in 2023. Despite challenges such as market access, low input quality, and environmental impacts, small-scale pond aquaculture is economically viable and plays a crucial role in fish production. The Buikwe and Wakiso districts demonstrated greater productivity and efficiency than did the Mpigi district, with notable variations in fish production and pond sizes. The study further highlights the need to improve market access, input quality, and income diversification through targeted interventions within the basin. Additionally, efforts should be made to optimize technical practices such as pond management, efficient feed management, optimal stocking and harvesting techniques as well as disease management and biosecurity.